Correlations between clinical severity, genotype and muscle pathology in limb girdle muscular dystrophy type 2A. Issue 10 (25th May 2007) - Fanin, M; Nardetto, L; Nascimbeni, A C; Tasca, E; Spinazzi, M; Padoan, R; Angelini, C
Abstract : Background: Limb girdle muscular dystrophy type 2A (LGMD2A) is characterised by wide variability in clinical features and rate of progression. Patients with two null mutations usually have a rapid course, but in the remaining cases (two missense mutations or compound heterozygote mutations) prognosis is uncertain. Methods: We conducted what is to our knowledge the first systematic histopathological, biochemical and molecular investigation of 24 LGMD2A patients, subdivided according to rapid or slow disease progression, to determine if some parameters could correlate with disease progression. Results: We found that muscle histopathology score and the extent of regenerating and degenerating fibres could be correlated with the rate of disease course when the biochemical and molecular data do not offer sufficient information. Comparison of clinical and muscle histopathological data between LGMD2A and four other types of LGMD (LGMD2B–E) also gave another important and novel result. We found that LGMD2A has significantly lower levels of dystrophic features (ie degenerating and regenerating fibres) and higher levels of chronic changes (ie lobulated fibres) compared with other LGMDs, particularly LGMD2B. These results might explain the observation that atrophic muscle involvement seems to be a clinical feature peculiar to LGMD2A patients. Conclusions: Distinguishing patterns of muscle histopathological changes in LGMD2A might reflect the effects of a disease-specific pathogenetic mechanism and provide clues complementary to genetic data.